PUBLIC – PRIVATE PARTNERSHIPS IN INDIAN EDUCATION - M.RAMESH (AJRBEM: ASIAN JOURNAL OF RESEARCH IN BUSINESS ECONOMICS AND MANAGEMENT, 2011)
The aim of education should be to teach us rather how to think, than what to think rather to improve our minds, so as to enable us to think for ourselves, than to load the memory with the thoughts of other men.” Education is the fourth necessity for man after food, clothing and shelter, in today’s competitive world. Education is indeed a powerful tool to combat the cut-throat competition that man is faced with at every junctures in life. The importance of education in India is indeed rising with passing time. Though India has always been a great source of learning for many years, it still needs to improve not just on the quality of education but also on the number of people being educated India has been a major centre for learning and many popular universities existed here. Even today, the country has some of the best Universities in the world. Besides, it is also facing many challenges in its primary education while striving to reach 100percent literacy. Through the Universal Compulsory Primary Education, maintaining the quality of education in rural areas has been difficult and Kerala is the only Indian state to achieve this goal. In today's world, studies are a biggest competition in the world. Education is not what it is supposed to be. The moral values are getting eroded. Social fabric is getting weakened. We are imparting theoretical knowledge based education. We have to make the children more aware on socialness. Even the information being given is very much non uniform in all the states. Education must make the student think, make them invent new ideas and not reinvent the same wheel. The education system in India puts more emphasis on the theoretical knowledge than the practical. A student from the very beginning of their of education are forced to mug up the things rather than to have free thoughts. In the higher studies as well the condition is the same. So more stress should be on the rational or practical knowledge that can be used when required. There are many obstacles to the successful provision of universal primary and secondary education